2016
DOI: 10.1128/aac.01509-15
|View full text |Cite
|
Sign up to set email alerts
|

Biofilms of Pathogenic Nontuberculous Mycobacteria Targeted by New Therapeutic Approaches

Abstract: Microbial infections of the cornea are potentially devastating and can result in permanent visual loss or require vision-rescuing surgery. In recent years, there has been an increasing number of reports on nontuberculous mycobacterial infections of the cornea. Challenges to the management of nontuberculous mycobacterial keratitis include delayed laboratory detection, low index of clinical suspicion, poor drug penetration, slow response to therapy, and prolonged use of antibiotic combinations. The ability of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 63 publications
0
47
0
Order By: Relevance
“…hominissuis tolerance of the antimicrobials. Since that report, another study also recently described effective cotreatment of M. chelonae and M. fortuitum biofilms with DNase I and antimicrobial agents (24), further demonstrating the importance of eDNA in NTM biofilms.…”
Section: Introductionmentioning
confidence: 88%
“…hominissuis tolerance of the antimicrobials. Since that report, another study also recently described effective cotreatment of M. chelonae and M. fortuitum biofilms with DNase I and antimicrobial agents (24), further demonstrating the importance of eDNA in NTM biofilms.…”
Section: Introductionmentioning
confidence: 88%
“…For the assessment of biofilm‐forming ability, M. abscessus 29904 was grown for 3–4 days in supplemented Middlebrook broth, standardized to 1 × 10 6 colony forming units/ml at optical density (OD) 600 = 0.1 (Aung et al, ), inoculated (200 μL) in 96‐well, flat–bottomed, sealed polystyrene plates, and incubated for 2, 4, and 8 days at 37 °C (Hall‐Stoodley & Lappin‐Scott, ). Biofilm formation was evaluated by measuring the biomass at each time point (Di Giulio, Traini, Sinjari, Nostro, Caputi, & Cellini ); after removing the planktonic phase, wells were washed with PBS, dried, and stained with 0.1% safranin solution (1 min).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that M. fortuitum and M. chelonae readily form drug-resistant biofilms, irregular finger-like projections and microcolonies (Figure-2), suggesting a probable cause of poor treatment compliance to conventional antibiotics 48 . Studies have concluded that there is a significant eDNA release with M. fortuitum and chelonae biofilms, which protect the organisms from the antibiotics: however, adding DNase can boost the efficacy of available antibiotics 33,48,49 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that M. fortuitum and M. chelonae readily form drug-resistant biofilms, irregular finger-like projections and microcolonies (Figure-2), suggesting a probable cause of poor treatment compliance to conventional antibiotics 48 . Studies have concluded that there is a significant eDNA release with M. fortuitum and chelonae biofilms, which protect the organisms from the antibiotics: however, adding DNase can boost the efficacy of available antibiotics 33,48,49 . There was a pioneer report to show that AMB keratitis is a biofilm mode of growth in an experimental mouse keratitis model and suggested that poor clinical outcomes of AMB infections might be due to its presence of biofilm matrix causing a barrier for antibiotic penetration and resistance 33 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation